2010
DOI: 10.1103/physrevb.81.045401
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory with nonlocal correlation: A key to the solution of the CO adsorption puzzle

Abstract: We study the chemisorption of CO molecule into sites of different coordination on ͑111͒ surfaces of late 4d and 5d transition metals. In an attempt to solve the well-known CO adsorption puzzle, i.e., discrepancies of adsorption site preferences with experiment which appear in the standard density functional theory calculations, we have applied the relatively new van der Waals-density functional of nonlocal correlation. In all considered cases this reduces or completely solves the site preference discrepancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
88
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 29 publications
8
88
1
Order By: Relevance
“…This explains the discrepancies found between experiment and calculation, where DFT fails to predict the experimentally observed atop-site occupation at low coverage for CO adsorption on both native Pt(111) and Rh(111) (36,37). To reduce or solve completely such site preference discrepancies in DFT, one can use the newly developed van der Waals-density functional (vdW-DF) of nonlocal correction as shown by Lazi c et al (38). In addition to this, recent calculations based on many-body perturbation theory, including the exact exchange and correlation energy using the random phase approximation (RPA), correctly predict the atop site to be the lowest energy adsorption configuration for Pt(111) and Rh(111) (39).…”
Section: Resultsmentioning
confidence: 99%
“…This explains the discrepancies found between experiment and calculation, where DFT fails to predict the experimentally observed atop-site occupation at low coverage for CO adsorption on both native Pt(111) and Rh(111) (36,37). To reduce or solve completely such site preference discrepancies in DFT, one can use the newly developed van der Waals-density functional (vdW-DF) of nonlocal correction as shown by Lazi c et al (38). In addition to this, recent calculations based on many-body perturbation theory, including the exact exchange and correlation energy using the random phase approximation (RPA), correctly predict the atop site to be the lowest energy adsorption configuration for Pt(111) and Rh(111) (39).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, CO adsorption on Pt surfaces is indeed a non-trivial system to be calculated with DFT in general as the approach usually tends to overestimate the 3-fold hollow sites over atop sites, which in low temperature experiments were found to be preferred. As our aim is to investigate the co-adsorption of CO and OH, here we point the reader to the extensive discussions about the so-called "CO/Pt(111) puzzle" [41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with previous ab initio results. 76,[78][79][80] Multireference singles and doubles configuration interaction (MRSDCI) calculations resulted in that the bridge structure is about 0.98 eV stronger than the atop structure. 76 Collision-induced dissociation experiments also showed that the bridge structure is the most stable structure for the CO−Pt 2 anion.…”
Section: Co Interaction With Pt Atom and Dimermentioning
confidence: 99%